What is at stake? Exploring the moral experience of stigma with Indian-Australians and Anglo-Australians living with depression - Brijnath, Bianca; Antoniades, J. (2018)
© 2018, The Author(s) 2018. This article applies the framework of moral experience to examine the cultural experience of stigma with Indian-Australians and Anglo-Australians living with depression in Melbourne, Australia. To date few studies have examined this dynamic in relation to mental illness and culture, and no studies have applied this framework in a culturally comparative way. Based on 58 in-depth interviews with people with depression recruited from the community, we explicate how stigma modulates what is at stake upon disclosure of depression, participants’ lived experience following that disclosure, and how practices of health-seeking become stigmatised. Findings show that the social acceptance of depression jars against participants’ experience of living with it. Denialism and fear of disclosure were overwhelming themes to emerge from our analysis with significant cultural differences; the Anglo-Australians disclosed their depression to family and friends and encountered significant resistance about the legitimacy of their illness. In contrast, many Indian-Australians, especially men, did not disclose their illness for fear of a damaged reputation and damaged social relations. For Indian-Australians, social relations in the community were at stake, whereas for Anglo-Australians workplace relations (but not community relations) were at stake. Participants’ experiences in these settings also influenced their patterns of health-seeking behaviors and age and inter-generational relationships were important mediators of stigma and social support. These findings illuminate how stigma, culture, and setting are linked and they provide critical information necessary to identify and develop customised strategies to mitigate the harmful effects of stigma in particular cultural groups.